Psychological and Physiological Impact of Indoor Plants and Their Maintenance - Ananya Chamola; Shruti Apurva; Adithi Rao; Chaitali Ghosh (International Journal of Indian Psychȯlogy, 2022)
Majority of indoor or house plants are cultivated for decorative or ornamental purposes and are typically grown within our homes, businesses, and retail spaces. It has been hugely reported that besides aesthetics, they also exhibit several physical and psychological benefits. They bring peace and positive vibes to our residence and workplace and also purify the surroundings by reducing indoor air pollution by absorbing some volatile organic compounds. During the COVID-19 pandemic, people realised the significance of the environment and its resources which eventually made these indoor plants even more popular. The present survey-based study therefore took into account the psychological, physiological and the maintenance aspect, and interconnected and established a correlation amidst the three aspects. The study also helped us find the benefits of indoor plants on people living inside enclosed spaces, especially during the recent pandemic. 86% of the respondents reported that their stress levels decreased in the presence of indoor plants, and 52% agreed that houseplants are better than artificial air purifiers. As a result, these are presently employed to enhance mental health as well as alternatives for beautifying and enhancing the aesthetic value of homes and workplaces.